Avaliação do coeficiente de atrito de braquetes metálicos e estéticos com fios de aço inoxidável e beta-titânio - Braga, Cristine Pritsch (2004)
An important factor that defines the effectiveness of the appliances is the friction between the surfaces of wires and brackets. Thus, that study was developed in order to investigate the static friction coefficient between stainless steel and beta-titanium wires (TP Orthodontics) and the stainless steel brackets (Dynalock® - Unitek), esthetic brackets with a stainless steel slot (Clarity® - Unitek) and conventional esthetic brackets (Allure® - GAC). For this purpose, an equipment was built in the Department of Mechanical Engineering and Mechatronics at PUCRS. It should be stressed that before the tests began, the Method Error was quantified and it was found that there was no significant interference (p>0,05) by the factor operating in the measurements. From then, the friction coefficient could be calculated, obtained by dividing friction force by the normal load. The statistic method used in these study was Analysis of Variance (ANOVA) and Multiple Comparison test (Tukey). It was found that: 1) the combination with the lowest friction coefficient was constituted by the stainless steel wire against the Dynalock® bracket, and the one with the highest friction coefficient was that of the Allure® bracket with the beta-titanium wire; 2) the beta-titanium wire presented a friction coefficient that was significantly higher than the stainless steel wire; 3) the Dynalock® bracket did not present any significant differences in relation to the friction coefficient of the Clarity® bracket when the wire used was of beta-titanium. However, when the wire tested was of stainless steel, the Dynalock® bracket presented a significantly lower friction coefficient. The Clarity® bracket presented a significantly lower friction coefficient than the Allure® bracket.